Exposure to benzene in gas station workers: An integrative literature review (Research, Society and Development, 2021)
Exposure to benzene causes damage to health, a fact that has made it a target of the attention of health surveillance agencies around the world. This compound is capable of causing damage hematological, genotoxic and cancer development. The purpose of this study is to carry out the bibliographic survey about the toxic effects of exposure to benzene in workers of gas station. This is an integrative literature review with qualitative approach. Was performed bibliographic survey in the Scielo, LILACS, LA Reference and PubMed, from August 2010 to December 2020, in Portuguese, English and Spanish. Analysis of the publications showed that the most appropriate biomarker for monitoring occupational exposure to benzene is the phenylmercapturic acid. Hematological changes and effects genotoxic substances are also often found in exposed individuals and are useful as effect biomarkers. It is concluded that the workers of resale posts of fuels are susceptible to a variety of health hazards as a result of exposure to benzene, and that labor legislation needs to be updated in order to minimize these damage.